(untitled) (Avocetta, 2025)
Review of Tveit B.O. 2024. A Birdwatcher’s Guide to Norway. Where, When and How to find Scandinavia’s most sought-after birds. 2nd ed. Ørn Forlag & Pelagic Publishing. 460 pp., many color photos and maps.